2017
DOI: 10.1108/bfj-04-2017-0210
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of milk consumer preferences

Abstract: Purpose The purpose of this paper is to report a survey in random-selected supermarkets in Italy in order to identify the attitudes and perceptions of consumers toward milk and in particular toward donkey milk. Design/methodology/approach The analysis was conducted through Google Forms platform of docs.google interviews with a sample of 705 consumers who were given a questionnaire to collect information about their economic status and their attitudes toward milk and special milk consumption. Findings The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 32 publications
3
22
0
1
Order By: Relevance
“…A strand of literature explored gender behavior linked to social and psychological issues, observing difference in "charitable giving, bargaining, and household decision making" (Andreoni & Vesterlund, 2001) as well as in generosity (Cox & Deck, 2006), in impulse purchase (Dittmar et al, 1995) and in social preferences (Croson & Gneezy, 2009). Concerning agro-food sector, several studies have been addressed to highlight whether differences exist among males and females in purchasing behaviors or consumption for specific food products (Allegra et al, 2012;Lanfranchi et al, 2017) and even for locally produced food (Girgenti et al, 2016;Bazzani et al, 2017;Giampietri et al, 2018). Differences between males and females in researches that related gender to food were found by Rappoport et al (1993).…”
Section: Introductionmentioning
confidence: 99%
“…A strand of literature explored gender behavior linked to social and psychological issues, observing difference in "charitable giving, bargaining, and household decision making" (Andreoni & Vesterlund, 2001) as well as in generosity (Cox & Deck, 2006), in impulse purchase (Dittmar et al, 1995) and in social preferences (Croson & Gneezy, 2009). Concerning agro-food sector, several studies have been addressed to highlight whether differences exist among males and females in purchasing behaviors or consumption for specific food products (Allegra et al, 2012;Lanfranchi et al, 2017) and even for locally produced food (Girgenti et al, 2016;Bazzani et al, 2017;Giampietri et al, 2018). Differences between males and females in researches that related gender to food were found by Rappoport et al (1993).…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers [69] show that Chinese consumers are significantly influenced by the country-of-origin of milk and dairy products, trusting them more than the local products, while the preference for a specific country is guided by consumer familiarity and experience with the products, ethnocentrism, and animosity, and even some cultural value differences. For the Italian consumers, the low price and high availability in the supermarkets of cows' milk are main reasons for consumption, while the health benefits of the donkey milk are seen as superior, but the difficulty of finding it in the supermarkets proves to be a significant barrier [70].…”
Section: Factors Influencing the Consumer Choice Of Milk And Dairymentioning
confidence: 99%
“…Credence attributes (such as animal welfare assurance, environmental stewardship, organic production, or country of origin) and extrinsic cues (such as brand name, price, nutritional label, precautionary label) influence purchase decisions. In the context of milk purchases, it has been reported that important determinants include price, accessibility, being free from allergens [15], health claims such as nutrient and other function claims [16], packaging and brand image [17]. Such attribute/cue selection and prioritization processes are heterogeneous among different market segments and such decisions making processes are culturally embedded [18].…”
Section: Credence Attributes and Extrinsic Cuesmentioning
confidence: 99%